Design and implementation of a mobile-controlled IoT smart pet feeder for busy pet owners - Zainuddin, Ahmad Anwar; Mahazir, Muhammad Nur Badri; Adanan, Mohamad Aiman Akim; Mohd. Tamrin, Mohd. Izzuddin; Zulkfli, Mohammad Adam Haikal; Samsudin, Muhammad Hazim Amin (Penteract Technology, 2024)
Pet owners often struggle to maintain their pets' nutrition due to tight schedules and busy lifestyles, making it difficult to ensure pets receive adequate care. To address this issue, this paper proposes a system that integrates IoT technology, in the form of a smart pet feeder, with mobile applications. The system uses a mobile application as a remote control for the smart pet feeder, allowing owners to monitor food consumption and establish automated feeding schedules, ensuring pets are fed on time, even when the owner is away. The system consists of a mobile application and a smart pet feeder as the hardware component, enabling users to manage feeding remotely while offering real-time monitoring and scheduling features. A survey conducted among the IIUM community identified key features, such as automated feeding schedules and real-time monitoring, which were incorporated into the system's design. The system architecture was developed to illustrate the structure and operation of the solution. This work provides a comprehensive solution to the common challenges pet owners face, ensuring their pets' nutrition and well-being are maintained withgreater convenience and reliability.